Ru/Pd Complex and Its Monometallic Fragments as Catalysts for Norbornene Polymerization via ROMP and Addition - Cruz, Thaís R. [UNESP]; Masson, Gustavo H. C. [UNESP]; Amorim, Kelly A. E.; Machado, Antonio E. H.; Goi, Beatriz E. [UNESP]; Carvalho-Jr, Valdemiro P. [UNESP] (MDPI, 2022)
The [Ru(PPh3)2Cl-piperidine(4-aminomethyl)] complex (mono-Ru) was synthesized from [Ru(PPh3)3Cl2] and 4-(aminomethyl)piperidine, whereas the [(PPh3)PdCl(Shiff-pip)] complex (mono-Pd) was obtained by reacting [Pd(PPh3)2Cl2] with its respective Schiff base ligand, both at a 1:1 molar ratio. The heterobimetallic [RuCl2(PPh3)2](μ-Schiff)Pd(PPh3)Cl] complex (Ru/Pd) was synthesized via a one-pot, three-component reaction of mono-Ru, [(Pd(PPh3)2Cl2] and salicylaldehyde. All complexes were fully characterized by FTIR, UV-Vis, and NMR spectroscopy, as well as elemental analysis, MALDI-TOF mass spectrometry, cyclic voltammetry, and computational studies. Ru/Pd was able to polymerize norbornene (NBE) by two different mechanisms: ROMP and vinyl polymerization. The Ru fragment was active for ROMP of NBE, reaching yields of 68 and 31% for mono-Ru and Ru/Pd, respectively, when the [NBE]/[Ru] = 3000 molar ratio and 5 μL EDA addition were employed at 50 °C. The poly(norbornene) (polyNBE) obtained presented an order of magnitude of 104 g mol−1 and Ð values between 1.48 and 1.79. For the vinyl polymerization of NBE, the Pd fragment was active using MAO as a cocatalyst, reaching a yield of 47.0% for Ru/Pd and quantitative yields for mono-Pd when [Al]/[Pd] = 2500 and [NBE]/[Pd] = 20,000 molar ratios were employed, both at 60 °C.
Keywords: bifunctional catalysts; heterobimetallic complexes; metathesis; palladium; ruthenium